2020
DOI: 10.1186/s13023-020-01456-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Haemophilia Care in Europe: 10 years of the principles of care

Abstract: Introduction: The European principles of care in haemophilia marked their first decade in 2018. These guiding principles were the beginning of the European Haemophilia Consortium (EHC) review of countries' adherence to these principles in 2009, 2012, 2015 and 2018. The aim of this paper was to examine the implementation of the principles and how they have impacted the evolution of care in the last decade, as well as to identify remaining gaps and proposes future directions. Methods: In 2018, the EHC distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“… 1 , 2 Yet, despite implementation since 2008 of the European Principles of Hemophilia Care (EPHC), 1 management practices, treatment access and patient education still vary in different European regions. 3 The 2020 European Hemophilia Consortium (EHC) survey revealed that Western Europe has benefitted more from improvements made due to EPHC implementation compared to Eastern Europe. 3 Access to different types of hemophilia care, including at-home treatments and prophylaxis, was also higher among Western European countries compared with Eastern European countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 2 Yet, despite implementation since 2008 of the European Principles of Hemophilia Care (EPHC), 1 management practices, treatment access and patient education still vary in different European regions. 3 The 2020 European Hemophilia Consortium (EHC) survey revealed that Western Europe has benefitted more from improvements made due to EPHC implementation compared to Eastern Europe. 3 Access to different types of hemophilia care, including at-home treatments and prophylaxis, was also higher among Western European countries compared with Eastern European countries.…”
Section: Introductionmentioning
confidence: 99%
“… 3 The 2020 European Hemophilia Consortium (EHC) survey revealed that Western Europe has benefitted more from improvements made due to EPHC implementation compared to Eastern Europe. 3 Access to different types of hemophilia care, including at-home treatments and prophylaxis, was also higher among Western European countries compared with Eastern European countries. 3 Notably, the European Hemophilia Network (EUHANET) reported that countries with the lowest number of Hemophilia Treatment Centers (HTCs) tend to be in Eastern Europe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected by EHC from 2009 to 2016 demonstrated a trend of increased access to CFCs in many Western and central European countries 30‐32 . During that time, access to treatment increased significantly, sometimes linked to increased home treatment, prophylaxis for adults, and availability of immune tolerance therapy.…”
Section: Historic Perspective (1970‐2010)mentioning
confidence: 99%
“…Comprehensive, integrated care provided by a multi-disciplinary team of experts improves outcomes and is widely recommended for people with haemophilia (PWH). [1][2][3][4][5][6] Although care models vary, the principles of management are consistent between countries.…”
Section: Introductionmentioning
confidence: 99%